The perk of writing: How expressive writing reduces depressive symptoms - Efendy Xu; Tara Yen Siang Tan; Hao Wang; Chen Sung Wong; KamYan Chong; Kususanto Ditto Prihadi (Intelektual Pustaka Media Utama, 2021)
This study aimed to examine types of expressive writing and the underlying themes that will lead to the reduction of depression symptoms. We hypothesized that positive experience writing will significantly reduce depressive symptoms as compared to other types of expressive writing. This study recruited 45 young adults (17 men, 28 women) between 20 and 28 years old to perform online expressive writing for a four-week period and fill in the Patient Health Questionnaire (PHQ-9) before and after the treatment. Our findings suggested that positive expressive writing led to a significantly greater reduction of depressive symptoms as compared to other types of expressive writing. The qualitative analysis showed that there are eight common themes in positive writing that might contribute to the reduction of symptoms: companionship, mattering, gratitude, positive emotions, energetic, motivation, relaxation, and delicious food. Limitations and implications of the findings are discussed.